Effect of Dietary Carotenoid on Egg Yolk Color and Singlet Oxygen Quenching Activity of Laying Hens - Sadao Kojima; Sakura Koizumi; Yukari Kawami; Yuna Shigeta; Ayako Osawa (The Journal of Poultry Science, 2022)
The effects of dietary carotenoids on egg yolk were investigated in this study. Forty Rhode Island Red (RR) and 40 Silky Fowl (SF) hens that were 60 weeks old were used. Hens of each breed were randomly divided into four dietary groups. One group was fed a basal diet (crude protein 17%, metabolizable energy 2800 kcal/kg) only, whereas the other groups received a specific additive, namely, paprika extract, marigold petal extract, or Paracoccus cell powder, in addition to the same basal diet. The color and carotenoid content of egg yolk and singlet oxygen quenching activity were measured after 4 weeks. The total carotenoid content, zeaxanthin content, and singlet oxygen quenching activity in the yolk differed significantly between breeds and between diets (two-way ANOVA). The lutein content in egg yolk was affected by breed and diet, as well as by the interaction between these two factors. Regarding the Roche Yolk Color Fan values, only the effect of diet was significant. In terms of objective egg yolk color, there was a significant difference in lightness and yellowness between breeds. The total carotenoid content was higher in SF than in RR in all the groups. Likewise, the levels of zeaxanthin and lutein in the yolk were higher in SF than in RR (P<0.05). The results of the present study suggest that dietary carotenoids are effective feed additives for laying hens, especially SF, to improve the color and singlet oxygen quenching activity of egg yolk.